Engineering a Reliable and Convenient SARS-CoV-2 Replicon System for Analysis of Viral RNA Synthesis and Screening of Antiviral Inhibitors - Yuewen Luo (American Society for Microbiology, 2021)
COVID-19 has caused a severe global pandemic. Until now, there has been no simple and reliable system available in a lower-biosafety-grade laboratory for SARS-CoV-2 virologic research and inhibitor screening.